2021
DOI: 10.1016/j.invent.2021.100405
|View full text |Cite
|
Sign up to set email alerts
|

Online consultations in mental healthcare during the COVID-19 outbreak: An international survey study on professionals' motivations and perceived barriers

Abstract: Introduction While the general uptake of e-mental health interventions remained low over the past years, physical distancing and lockdown measures relating to the COVID-19 pandemic created a need and demand for online consultations in only a matter of weeks. Objective This study investigates the uptake of online consultations provided by mental health professionals during lockdown measures in the first wave of the COVID-19 pandemic in the participating countries, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 25 publications
5
51
0
3
Order By: Relevance
“…Overall, our findings correspond to other research targeting the views and experiences of psychotherapists. Among European psychotherapists having mainly positive experiences with online consultations during the COVID-19 pandemic, De Witte et al ( 43 ) reported several barriers that might hinder implementation, such as data security issues or concerns about relational aspects, for instance impersonality and fostering a therapeutic alliance. In a study by Sander et al ( 86 ), German professionals reported having little experience or knowledge about internet-delivered interventions and the most frequently anticipated barriers were too severe symptoms of patients, the feared neglect of face-to-face contacts and insufficient technical equipment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, our findings correspond to other research targeting the views and experiences of psychotherapists. Among European psychotherapists having mainly positive experiences with online consultations during the COVID-19 pandemic, De Witte et al ( 43 ) reported several barriers that might hinder implementation, such as data security issues or concerns about relational aspects, for instance impersonality and fostering a therapeutic alliance. In a study by Sander et al ( 86 ), German professionals reported having little experience or knowledge about internet-delivered interventions and the most frequently anticipated barriers were too severe symptoms of patients, the feared neglect of face-to-face contacts and insufficient technical equipment.…”
Section: Discussionmentioning
confidence: 99%
“…As a starting point, van Daele et al (96) have recently formulated an association with the European Federation of Psychologists' Associations (EFPA) general guidelines for mental health workers, health services, regulatory agencies as well as developers to promote the implementation of evidencebased EMH services. The strong need for training and further education also becomes visible in a recent study by De Witte et al (43), in which participants were asked whether they received any form of training on online consultations about EMH. Results revealed that only 11% of the sample received a form of training, however, only half of these training programs were specific to EMH and lasted just <4 h in every second case.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find RCTs that tested the hypothesis that online or blended DBT is superior or at least equally effective as standard, face-to-face DBT. At the same time, we observe a steady increase of online or blended care in clinical practice, with the coronavirus pandemic as a catalyst [ 7 , 26 , 27 ]. In the absence of sufficient evidence, we think it is advisable to return to face-to-face contact as soon as possible and to remain aware of selection bias, confirmation bias and technology optimism.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the DBT skills training is evolving from a treatment mode for suicidal patients with BPD to a transdiagnostic intervention [ 9 ]. Telepsychology is increasingly being used in DBT supervision and -training for professionals [ 19 25 ] and in mental health care in general [ 26 , 27 ]. Arguments both in favor and against such an evolution can be made.…”
Section: Introductionmentioning
confidence: 99%